The Influence of Purslane Plant Extract (Portulaca oleracea) Against Molting Frequency And Giant Prawns Growth (Macrobrachium rosenbergii) Stadia Juvenile - Marits Alhan Urma Indra Roisy; Samsundari Sri; Ganjar Adhywirawan Sutardjo3 (Universitas Muhammadiyah Malang, 2023)
Galah prawns (Macrobrachium rosenbergii) are the largest freshwater shrimp with high economic value. However, the process of prawns cultivation (Macrobrachium rosenbergii) often encounters obstacles, especially on the ability of molting and slow growth rate. One of the factors that influence is the hormone ecdysterone in the body of the prawns (Macrobrachium rosenbergii). Efforts to improve molting and growth by adding oral hormone ecdysterone obtained from the extraction of purslane plants (Portulaca oleracea). Purslane plant (Portulaca oleracea) one of the plants containing ecdysterone with levels reaches 720 mg / l. The method used was experimental method, Completely Randomized Design (RAL) 6 treatment ie P1 (0 mg / g body weight), P2 (5 mg / g body weight), P3 (10 mg / g body weight), P4 (15 mg / g body weight), P5 (20 mg / g body weight), and P6 (25 mg / g body weight) and 3 replications. Data were analyzed using diversity analysis (ANAVA), and if there were differences followed by BNT test. The results showed that the effect of giving of Krokot (Portulaca oleracea) extract on Molting Frequency and Gava Prawn Growth (Macrobrachium Rosenbergii) Stadia Juvenil had no significant effect on molting frequency where F. Calculate 2,7429 <from F.Table 5% (3.11) F . Table 1% (5.06) and growth F. Calculate Absolute Weight 0.3516 <of from F. Table 5% (3.11) F. Table 1% (5.06), and F. Calculate Length F. Calculate 1,918 <of from F. Table 5% (3.11) F. Table 1% (5.06). The water quality of giant prawns for 30 is temperature ranging from 24˚C-30˚C, dissolved oxygen 4,6-8,1 mg / l, and pH ranges from 8,4 to 9,0.